COMPARISON OF LAPAROSCOPIC CHOLECYSTECTOMY WITH AND WITHOUT ABDOMINAL DRAIN: A STUDY IN MTI-LADY READING HOSPITAL PESHAWAR - WAJID, .; NAEEM , H; KHAN , U; NOOR , I; SAFIULLAH , T; ALAM , Z; SHUJA , H; GUL, N (Biological and Clinical Sciences Research Journal, 2024)
Laparoscopic cholecystectomy is the standard treatment for gallbladder disease. The role of abdominal drainage in this procedure remains controversial, with concerns about its impact on pain, infection rates, and recovery time. Objective: .This study aimed to compare the outcomes of laparoscopic cholecystectomy performed with and without abdominal drainage. Methodology: This was conducted in the surgical ward of MTI Lady Reading Hospital, Peshawar, from January 2024 to July 2024. One hundred twenty patients undergoing elective laparoscopic cholecystectomy for gallbladder disease were randomly allocated into two groups: Group A (with drain, n=60) and Group B (without drain, n=60). Postoperative outcomes including pain, wound infection, nausea, and hospital stay were assessed. Results: The mean age was 49.12 ± 18.56 years for Group A and 51.70 ± 13.69 years for Group B. Postoperative pain scores (VAS) were higher in Group A (4.75 ± 1.62) than to Group B (3.63 ± 1.10, p=0.0001). Wound infections were more frequent in Group A (15%) than in Group B (3.3%, p=0.02). Postoperative nausea and vomiting occurred in 25% of Group A patients versus 8.3% in Group B (p=0.01). Hospital stay was considerably longer in Group A (3.13 ± 1.50 days) compared to Group B (2.15 ± 0.84 days, p=0.0001). Conclusion: Laparoscopic cholecystectomy without abdominal drainage had better postoperative outcomes than with drainage.